Making EU Foreign Policy National Preferences, European Norms and Common Policies - Thomas, Daniel C.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2011)
A novel explanation of how EU member states overcome their divergent preferences to reach agreement on common foreign policies, with fourteen in-depth case studies covering diplomatic and security issues, enlargement, trade, development and environmental protection.
Keywords: European Union; International relations; Comparative politics; Globalization; Diplomacy; Political science; European Union Politics; International Relations; Comparative Politics; Globalization; Diplomacy; Political Science